Impact of COVID-19 on Rural Tourism in Nepal (Patan Pragya, 2021)
This paper has focused upon the rural tourism in Nepal and the impacts of COVID-19 on its development. In Nepal tourism mostly occurs in rural environments and involves rural experiences. Wonderful rural cultures and traditional farming are attracting tourists in the rural areas. The villages of Nepal have their own unique natural and cultural dimensions. The fresh environment, natural and cultural artifacts, and the lifestyle of the local people are the main things to experience in the villages. Greatest potential benefit of rural tourism is its ability to generate money, which can translate into numerous positive economic opportunities for locals and their communities. But the COVID-19 pandemic has had a significant adverse impact on most businesses including rural tourism. Before COVID-19, rural tourism had become one of the most important activities to generate income in some rural areas of Nepal. But now all activities of rural tourism are in coma. Thus, in the post COVID-19 scenario, the very survival of the rural tourism industry will become the biggest challenge because there was no specific preparedness strategy in case of any crisis of this scale. Some measures are suggested to address the challenges and help prepare the strategy.